Pengetahuan Dengan Sikap Tentang Kesehatan Reproduksi (Studi Cross Sectional pada Mahasiswa Non Kesehatan Unissula Semarang) - Siti Thomas Zulaikhah; Ratnawati Ratnawati; Febiandika Istyoratih (FORIKES, 2020)
Introduction: Knowledge of reproductive health for adolescents is essential, with correct information, it is expected that adult have responsible attitudes and behaviors regarding the reproductive process. Students are the transition period between late adolescence to maturity, where the age of sexual maturity reaches its peak condition. Health students get material about reproductive health in their curriculum, while non-health students don't get information about it in their curriculum. This study aims to determine the relationship of reproductive health knowledge with reproductive health attitudes in non-health students. Methods: Observational analytic research with a cross-sectional design, data obtained from a questionnaire of knowledge and attitudes towards reproductive health in 44 non-health students at Sultan Agung Islamic University. Furthermore, the Chi-Square test to determine the relationship between variables. Results: The highest age at 21 years was 14 people (31.8%) while the youngest age at 18 years was two people (4.5%). The male sex was 26 people (59.1%), and the female sex was 18 people (40.9%). Respondents' knowledge about reproductive health was 34%, quite 18.2% and good 47.7%. Reproductive health attitudes of respondents were positive 65.9% and negative 34.1%. The results of the analysis with chi-square obtained p-value 0.032 (